„Vy jste dole, my nahoře!“: Sociální a etnické hranice v základní škole - Vorlíček, Radek (Lidé města, 2024)
The article explores the dynamics of social marginality and dominance in educational settings. Special attention is paid to the role of schools in the process of boundary constructions. The article deals with social distance dynamics among pupils in elementary school, and observes how these dynamics strengthen or weaken their position in the hierarchy. The text describes social interaction in a group of children, and records the context in which the inclusion or exclusion of those who are seen as the bearers of an identity other than the group dominant identity takes place, and whether it has the character of ethnic or social class. The article is based on long-term, qualitative, inductive, and ethnographic fieldwork. The central method of the fieldwork was ethnographic observation. To large degree, the research was conducted in the framework of interactionism. The article sheds light on many aspects of social exclusion in educational settings and on the obstacles of educational research.